Urethral luminal epithelia are castration‐insensitive cells of the proximal prostate - Joseph, Diya B.; Henry, Gervaise H.; Malewska, Alicia; Iqbal, Nida S.; Ruetten, Hannah M.; Turco, Anne E.; Abler, Lisa L.; Sandhu, Simran K.; Cadena, Mark T.; Malladi, Venkat S.; Reese, Jeffrey C.; Mauck, Ryan J.; et al. (The Prostate, 2020)
Background Castration‐insensitive epithelial progenitors capable of regenerating the prostate have been proposed to be concentrated in the proximal region based on facultative assays. Functional characterization of prostate epithelial populations isolated with individual cell surface markers has failed to provide a consensus on the anatomical and transcriptional identity of proximal prostate progenitors. Methods Here, we use single‐cell RNA sequencing to obtain a complete transcriptomic profile of all epithelial cells in the mouse prostate and urethra to objectively identify cellular subtypes. Pan‐transcriptomic comparison to human prostate cell types identified a mouse equivalent of human urethral luminal cells, which highly expressed putative prostate progenitor markers. Validation of the urethral luminal cell cluster was performed using immunostaining and flow cytometry. Results Our data reveal that previously identified facultative progenitors marked by Trop2, Sca‐1, KRT4, and PSCA are actually luminal epithelial cells of the urethra that extend into the proximal region of the prostate, and are resistant to castration‐induced androgen deprivation. Mouse urethral luminal cells were identified to be the equivalent of previously identified human club and hillock cells that similarly extend into proximal prostate ducts. Benign prostatic hyperplasia (BPH) has long been considered an “embryonic reawakening,” but the cellular origin of the hyperplastic growth concentrated in the periurethral region is unclear. We demonstrate an increase in urethral luminal cells within glandular nodules from BPH patients. Urethral luminal cells are further increased in patients treated with a 5‐α reductase inhibitor. Conclusions Our data demonstrate that cells of the proximal prostate that express putative progenitor markers, and are enriched by castration in the proximal prostate, are urethral luminal cells and that these cells may play an important role in the etiology of human BPH.